Mecanismos inmunoregulatorios mediados por la interleuquina 10 (IL-10) en la enfermedad de Chagas experimental - Pino Martínez, Agustina María (2016)
The overall objective of this thesis was to study the relationship between IL-10 and the mechanisms of resistance to Trypanosoma cruzi (T. cruzi), the causative agent of Chagas disease. For this, we used a model of experimental infection with T. cruzi in mice deficient in IL-10 (IL-10 KO) from Balb/c background. Unexpectedly, we found higher parasitemia levels, greater weight loss and mortality in mice deficient in IL-10, compared with WT mice infected with T. cruzi strains of high and moderate virulence. The kinetics of T cells in spleen and peripheral blood showed that infected IL-10 KO mice failed to expand the relative number of spleen and total circulating CD8+ T cells, a phenomenon observed from 21 dpi in WT mice. CD8+ T cells from IL-10 KO mice had diminished effector functions (cytotoxic potential and IFN-γ production) and decreases ex vivo proliferative response than those of WT mice, despite the increased producing of IL-2 by the latter. At 21 dpi, in the absence of IL-10, CD8+ T cells failed to reach critical infected organs such as the heart. Consistent with this, IL-10 KO mice presented higher parasite burden in heart tissue than WT mice, but not in quadriceps. At chronic infection (5 months pi.), the extension and number of infiltrates decreased globally, but the IL-10 still appeared to be required to drive the CD8+ T cells accumulation in target tissues. Hystopathological studies of cardiac and skeletal tissues confirmed that IL-10 is involved in controlling inflammation, preventing irreversible damage to the muscle fibers. Adoptive transfer assays showed an improvement in controlling parasitemia in mice receiving CD8+ T cells from both infected WT as IL-10 KO mice. This finding shows that the lower resistance to T. cruzi seen in IL-10 KO mice correlates with the lack of expansion of CD8+ Tcells and with the absence of IL-10 produced by this cell subpopulation. In conclusion, during acute infection with T. cruzi, IL-10 plays a previously unrecognized immunostimulatory role on CD8+ T cells (the most relevant lymphocyte population for the control of intracellular parasites). Understanding the mechanism that control the effector function of this cell population is critical to understand factors involved in the susceptibility to Chagas disease, and for the rational design of effective strategies for the prophylaxis against T. cruzi